A collisional model for AFM manipulation of rigid nanoparticles - Gnecco, Enrico (Beilstein Journal of Nanotechnology, 2010)
The trajectories of differently shaped nanoparticles manipulated by atomic force microscopy are related to the scan path of the probing tip. The direction of motion of the nanoparticles is essentially fixed by the distance b between consecutive scan lines. Well-defined formulas are obtained in the case of rigid nanospheres and nanowires. Numeric results are provided for symmetric nanostars. As a result, orienting the fast scan direction perpendicular to the desired direction of motion and reducing b well below the linear size of the particles turns out to be an efficient way to control the nanomanipulation process.
Keywords: atomic force microscopy; nanomanipulation; nanoparticles